Changes to hepatic tissue oxygenation, abdominal perfusion and its association with enteral feeding with liberal transfusion threshold in anaemic preterm infants: A prospective cohort study. Issue 8 (18th May 2020) - Jani, Pranav; Lowe, Krista; Hinder, Murray; Galea, Claire; D'Çruz, Daphne; Badawi, Nadia; Tracy, Mark
Abstract : Background and Objectives: In anaemic preterm infants who receive packed red blood cell (PRBC) transfusions, changes to mesenteric tissue oxygenation and perfusion have been reported using a restrictive haemoglobin (Hb)‐based threshold. We aimed to investigate changes to hepatic tissue oxygenation and abdominal blood flow after PRBC transfusion and its association with enteral feeding using a liberal Hb threshold (as shown in Table 1 ). Material and Methods: We prospectively studied a cohort of preterm infants born at < 32 weeks' gestation who received at least one PRBC transfusion and monitored them immediately before (Time 1), immediately after (Time 2) and 24 hours after transfusion (Time 3) . Data obtained included physiological parameters, the hepatic tissue oxygenation index and pulsed Doppler ultrasound measurements in the abdominal arterial circulation. Additionally, the effects of withholding enteral feeds were investigated. Results: We monitored 50 PRBC transfusion episodes in 40 preterm infants, in whom the mean gestational age was 26.72 weeks (±1.6 weeks) and the mean birth weight was 855.25 g (±190.7 g). We observed significant changes to pulsed Doppler measurements in abdominal arterial circulation (coeliac artery mean peak systolic velocity Time 2 [75.08 cm/sec] versus Time 3 [71.13 cm/sec]; mean end‐diastolic velocity Time 2 [15.71 cm/sec] versus Time 3 [13.76 cm/sec]; mean resistive index Time 2 0.78 versus Time 3 0.80, right renal artery mean peak systolic velocity Time 1 58.28 cm/sec versus Time 2 50.97 cm/sec, left renal artery mean peak systolic velocity Time 1 49.20 cm/sec versus Time 2 45.40 cm/sec), but not to hepatic tissue oxygenation after PRBC transfusion (Time 1 mean 53.66 [SD, 13.34]; Time 2 mean 54.93 [SD, 9.3]; Time 3 mean 55.64 [SD, 12.86]) . There were no changes to hepatic tissue oxygenation or mesenteric blood flow from withholding enteral feeds during PRBC transfusion. There were no local adverse effects from hepatic tissue oxygenation monitoring. Conclusion: In mildly anaemic preterm infants, when allowing a liberal Hb threshold‐based trigger for PRBC transfusion, changes in abdominal arterial circulation were present, but not in hepatic tissue oxygenation. Withholding enteral feeds during PRBC transfusion had no impact on hepatic tissue oxygenation or mesenteric flows.